2020
DOI: 10.1111/edt.12633
|View full text |Cite
|
Sign up to set email alerts
|

A cross‐sectional evaluation of knowledge among Chinese dentists regarding the treatment of traumatic injuries in primary teeth

Abstract: Background/Aim Injuries to the primary dentition affect children's esthetics, function, and mental health. They may also affect the development of the permanent teeth. The knowledge of dentists about deciduous tooth trauma is rarely evaluated. The aim of this study was to evaluate the knowledge and attitude of dentists in China regarding traumatic dental injuries to primary teeth. Material and Methods A self‐administered online questionnaire containing questions on demographic data and knowledge based on a cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…Close to half of participants said that they occasionally (47.6%) or rarely (20.4%) meet TDI in their daily work. That accommodate with the results of other investigations that said that traumatic injuries happen infrequently and at occasions when general practitioners are not ready for emergency management procedure (19)(20)(21)(22)(23) .…”
Section: For General Dental Practitionerssupporting
confidence: 68%
See 2 more Smart Citations
“…Close to half of participants said that they occasionally (47.6%) or rarely (20.4%) meet TDI in their daily work. That accommodate with the results of other investigations that said that traumatic injuries happen infrequently and at occasions when general practitioners are not ready for emergency management procedure (19)(20)(21)(22)(23) .…”
Section: For General Dental Practitionerssupporting
confidence: 68%
“…Getting a professional emergency managementat the site of accident is mandatory, that would decrease the time between avulsion and replantation,and Consequently decrease the risk of having internal and external root resorption (35,36) . 51% of GDPs chose the answer to splint avulsed teeth for 7 to 10 days , which was higher in comparison with other studies were only 10-30% had chosen this answer (15,22) . 136 (66.0%) of GDPs chose the answer that they would never do replantation for primary tooth, result was improved by the educational program to 182 (88.3%) which is consistent with (176) Nada A.…”
Section: For General Dental Practitionersmentioning
confidence: 70%
See 1 more Smart Citation
“…The deficit in clinical experience, limited number of contact hours, lack of a unified approach could contribute to the poor levels of knowledge on dental trauma reported by general dentists in recent studies. [11][12][13][14][15][16][17] The need for a core curriculum in DT was affirmed by the majority of institutions. The need for a separate trauma course was also a popular suggestion.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies including systematic reviews highlight the insufficient levels of knowledge possessed by dentists regarding the management of TDI around the world. [11][12][13][14][15][16][17] These reports suggested that additional clinical knowledge and skills would be required to improve confidence in managing TDI, especially when the injuries were more complex. It has been proposed that the insufficient level of knowledge and skills might be explained by a poor foundation in DT within Undergraduate (UG) dental programmes.…”
mentioning
confidence: 99%